Time-lapse full waveform inversion of vertical seismic profile data: Workflow and application to the CO2CRC Otway project - Egorov, A.; Pevzner, R.; Bóna, A.; Glubokovskikh, S.; Puzyrev, V.; Tertyshnikov, Konstantin; Gurevich, B. (American Geophysical Union, 2017)
©2017. American Geophysical Union. Vertical seismic profile (VSP) is one of the technologies for monitoring hydrocarbon production and CO 2 geosequestration. However, quantitative interpretation of time-lapse VSP is challenging due to its irregular distribution of source-receiver offsets. One way to overcome this challenge is to use full waveform inversion (FWI), which does not require regular offsets. We present a workflow of elastic FWI applied to offset vertical seismic profile data for the purpose of identification and estimation of time-lapse changes introduced by injection of 15,000 t of CO 2 -rich gas mixture at 1.5 km depth. Application of this workflow to both synthetic and field data shows that elastic FWI is able to detect and quantify the time-lapse anomaly in P wave velocity with the magnitude of 100-150 m/s.